Integration of a Commercial Barcode-Assisted Medication Dispensing System in a Teaching Hospital - Berdot, Sarah; Boussadi, Abdelali; Vilfaillot, Aurélie; Depoisson, Mathieu; Guihaire, Claudine; Durieux, Pierre; Le, Laetitia Minh Maï; Sabatier, Brigitte (Applied Clinical Informatics, 2019)
Objectives A commercial barcode-assisted medication administration (BCMA) system was integrated to secure the medication process and particularly the dispensing stage by technicians and the administration stage with nurses. We aimed to assess the impact of this system on medication dispensing errors and barriers encountered during integration process.Methods We conducted a controlled randomized study in a teaching hospital, during dispensing process at the pharmacy department. Four wards were randomized in the experimental group and control group, with two wards using the system during 3 days with dedicated pharmacy technicians. The system was a closed loop system without information return to the computerized physician order entry system. The two dedicated technicians had a 1-week training session. Observations were performed by one observer among the four potential observers previously trained. The main outcomes assessed were dispensing error rates and the identification of barriers encountered to expose lessons learned from this study.Results There was no difference between the dispensing error rate of the control and experimental groups (7.9% for both, p = 0.927). We identified 10 barriers to pharmacy barcode-assisted system technology deployment. They concerned technical (problems with semantic interoperability interfaces, bad user interface, false errors generated, lack of barcodes), structural (poor integration with local information technology), work force (short staff training period, insufficient workforce), and strategic issues (system performance problems, insufficient budget).Conclusion This study highlights the difficulties encountered in integrating a commercial system in current hospital information systems. Several issues need to be taken into consideration before the integration of a commercial barcode-assisted system in a teaching hospital. In our experience, interoperability of this system with the electronic health record is the key for the success of this process with an entire closed loop system from prescription to administration. BCMA system at the dispensing process remains essential to purchase securing medication administration process.
Keywords: electronic data processing; medication systems; medication errors; hospital information systems; integrated information systems; specific types; clinical information systems; pharmacy